Effectiveness of Physics Learning Tools using Blended Learning Model with Video Assistance on Momentum and Impulse Materials to Improve Problem Solving Ability of Students - Susilawati Susilawati; Aris Doyan; Izlayani Putri; Muhammad Taufik (AMPLITUDO : Journal of Science and Technology Innovation, 2022)
This study aims to determine the effectiveness of physics learning tools using blended learning model with video assistance on momentum and impulse materials to improve problem solving ability of students. The learning tools were developed using a 4D model which includes the stages of define, design, develop, and disseminate. Learning tools developed in the form of syllabus, lesson plans, student worksheets, learning videos, and problem solving ability instruments in the form of descriptions with a total of 5 questions. The research data was obtained from the results of a limited trial in the tenth grade MIPA 4 SMAN 1 Mataram with a total of 33 people. The data obtained from the next study were tested for the value of n-gain to find out the improvement in problem solving abilities. The results showed that the overall value of n-gain was 0.66 in the medium category. In addition, the n-gain analysis of each problem solving indicator shows that the indicators of recognizing problems and planning strategies have increased with the n-gain value being in the medium category, while the indicator implementing strategies and evaluating solutions has increased with the n-gain value being in the high category. These results indicate that the physics learning tools using blended learning model with video assistance on momentum and impulse materials is effective to improve problem solving ability of students.